Potato tuber simulated yield in climate change scenarios - Fagundes, Joelma Dutra; Streck, Nereu Augusto; Bisognin, Dilson Antonio; Schwantes, Ana Paula; Alberto, Cleber Maus (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this study was to simulate potato (Solanum tuberosum) tuber yield in different climate change scenarios of increased carbon dioxide concentration [CO2] and air temperature, considering symmetric and asymmetric increases in minimum and maximum daily air temperatures. Spitters model was used to simulate Asterix cultivar tuber yield considering two growing seasons (spring and fall) recommended for Santa Maria, state of Rio Grande do Sul, Brazil. In each growing season, five planting dates were evaluated in climate scenarios of a hundred years with no increase in [CO2] and temperature (current scenario), and in scenarios with doubling [CO2] and temperature increases of 0, 1, 2, 3, 4, 5 and 6ºC. A symmetric increase of 4ºC and an asymmetric increase of 5ºC in air temperature offset the yield beneficial effect of increasing [CO2] during spring, whereas increase in air temperature does not affect potato tuber yield during fall. Anticipating planting date in spring and delaying it in fall decrease the negative impact of the increasing air temperature on potato tuber yield.